Screening and detection of human papillomavirus (HPV) high-risk strains HPV16 and HPV18 in saliva samples from subjects under 18 years old in Nevada: a pilot study - Flake Colton; Arafa Jamal; Hall Alex; Ence Eryn; Howard Katherine; Kingsley Karl (BMC, 2012)
Abstract Background Human papillomaviruses (HPV) are oncogenic and mainly associated with cervical cancers. Recent evidence has demonstrated HPV infection in other tissues, including oral epithelia and mucosa. Although a recent pilot study provided new information about oral HPV status in healthy adults from Nevada, no information was obtained about oral HPV prevalence among children or teenagers, therefore, the goal of this study is to provide more detailed information about oral prevalence of high-risk HPV among children and teenagers in Nevada. Methods This retrospective study utilized previously collected saliva samples, obtained from pediatric dental clinic patients (aged 2 - 11) and local school district teenagers (aged 12-17) for high-risk HPV screening (n=118) using qPCR for quantification and confirmation of analytical sensitivity and specificity. Results A small subset of saliva samples were found to harbor high-risk HPV16 (n=2) and HPV18 (n=1), representing a 2.5% of the total. All three were obtained from teenage males, and two of these three samples were from White participants. Conclusions Although this retrospective study could not provide correlations with behavioral or socioeconomic data, this project successfully screened more than one hundred saliva samples for high-risk HPV, confirming both HPV16 and HPV18 strains were present in a small subset. With increasing evidence of oral HPV infection in children, this study provides critical information of significant value to other dental, medical, oral and public health professionals who seek to further an understanding of oral health and disease risk in pediatric populations.